Boys' Friendships During Adolescence: Intimacy, Desire, and Loss. (17th May 2013) - Way, Niobe
<x xml:space="preserve">Abstract</x> Longitudinal, mixed method research on friendships, conducted over the past two decades with Black, Latino, Asian, and European American boys, reveals three themes: (1) the importance for boys of being able to share their secrets with their close friends; (2) the importance of close friendships for boys' mental health; and (3) the loss of but continued desire for close male friendships as boys transitioned from middle to late adolescence. While boys often had intimate male friendships during early and middle adolescence, they typically lost such friendships by late adolescence, even though they continued to want them. Other researchers have reported similar patterns over the past century, suggesting a need to revise our conceptions of boys' friendships as well as of boys themselves.